CFD Analysis of a Venturi Injector System - Ersan, Ezgi; Taskiran, Ali; Karatas, Ahmet; Mohammed, Khalil Sheikh; Celik, Nevin (Mdpi, 2026)
This study presents a three-dimensional transient Computational Fluid Dynamics (CFD) analysis of a Venturi injector system used in a textile machine for removing excess water from fabrics after dyeing or washing processes. The main objective is to determine the optimum operating conditions by investigating the coupled effects of nozzle diameter and inlet pressure on pressure distribution, velocity field, and suction performance. Numerical simulations were performed for three nozzle diameters (dn = 14 mm, 15 mm, and 16 mm) and three inlet pressure values (Pi = 10 bar, 12 bar, and 15 bar). The results show that the Venturi injector performance is highly sensitive to the interaction between geometric and operating parameters. Increasing the inlet pressure from 10 bar to 15 bar resulted in approximately a 20% increase in maximum velocity and a 40-45% increase in vacuum pressure in the suction line. Among the investigated configurations, the nozzle diameter of 15 mm provided the most balanced flow structure, producing the highest pressure drop at the throat and the most stable suction behavior. Transient analyses revealed that suction formation occurs rapidly after flow initiation and remains stable throughout the operation period, indicating hydrodynamically stable injector performance under optimal conditions. The optimum operating point is identified as a nozzle diameter of 15 mm and an inlet pressure of 15 bar, where suction capacity is maximized and energy losses are minimized. The results provide a quantitative design guideline for the optimization of industrial Venturi injector system used in textile processing applications.
Keywords: venture injector; CFD analysis; drying textile